Divergent selection for shape of growth curve in Japanese quail. 2. Embryonic development and growth - Hyánková, L; Novotná, B; Knízetová, H; Horácková, S (British poultry science, 2004)
1. Embryonic growth and development were analysed using meat type lines of Japanese quail, HG and LG, divergently selected for shape of the growth curve. A total of 1020 embryos of generations 9, 10 or 13 were used for analysis. 2. Considerable inter-line differences were observed in the rate of embryonic development. When compared to HG, LG embryos appeared to be developmentally accelerated during the first 42 h of incubation (larger blastoderm diameter, more somites and higher frequency of more advanced Hamburger-Hamilton stages) as well as at the end of the prenatal period (more embryos with the yolk sac inside the body cavity, shorter incubation period). This corresponded with the trend in postnatal development. 3. Embryonic growth of both lines exhibited an exponential trend. However, considerable inter-line differences were noted in the rate of embryonic growth. Initial growth retardation compensated subsequently by a higher growth rate of HG vs LG quail, characterised the lines after hatching. The same growth pattern repeated three times during the prenatal period (between d 0 and 3, 3 and 8, and 8 and 16). 4. The repeated occurrence of transient decreases in growth rate of the developmentally delayed HG line could be associated with a delayed onset of genetically determined physiological functions mediating utilisation of nutrient supply. 5. Hence, different shapes of growth curves in two genotypes with similar growth potential reveal inter-line differences in physiological age persisting during the whole ontogenesis.
Keywords: Oviposition; Ovum; embryo nesavčí; kladení vajíček; ženské pohlaví; Coturnix; Kinetics; Animals; Time Factors; zvířata; časové faktory; morfogeneze; Female; kinetika; Morphogenesis; Embryo, Nonmammalian; ovum